Strategi Adaptasi Klinik Ananda Sehat Karangsono terhadap Persaingan Layanan Kesehatan di Era JKN - Purwadhi Purwadhi; Yani Restiani Widjaja; Agus Sunarto; Annisa Berlia Maharani (Jurnal Visi Manajemen, 2025)
This study aims to analyze the adaptation strategies of Ananda Sehat Karangsono Clinic in facing the competition in healthcare services in the era of the National Health Insurance (JKN). The background of this research is based on the increasingly fierce competition between healthcare facilities, both clinics and hospitals, in providing fast, efficient, and quality services according to JKN standards. The presence of the JKN program, which demands integrated, transparent, and technology-based services, encourages clinics to innovate to remain competitive and maintain operational sustainability. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, participatory observation, and documentation studies. Research informants included clinic leaders, healthcare workers, and administrative staff, thus providing a comprehensive perspective on the implemented adaptation strategies. The results show that Ananda Sehat Karangsono Clinic has integrated digital technologies, such as the Mobile JKN application and WhatsApp, to speed up the registration process, verify patient data, and facilitate communication. This innovation can improve the efficiency of service flows, reduce queues, and create a better service experience for patients. In addition, the clinic emphasizes the importance of patient satisfaction by improving service quality, speed, and friendliness of healthcare workers and support staff. The adaptation strategy implemented was not limited to technological aspects, but also encompassed operational efficiency and humanistic interpersonal services. Overall, the clinic's adaptation strategy was flexible and holistic, encompassing digitalization, strengthening internal management, and developing positive patient relationships. These findings confirm that the clinic was able to maintain competitiveness and service sustainability amidst the dynamics of the National Health Insurance (JKN) and the digitalization of the healthcare system.